Effects of dietary feed LP20 (Heat-Killed Lactobacillus plantarum) on growth performance and health of juvenile striped catfish (pangasianodon hypophthalmus) : - Myo, Halley Nay (Trường Đại học Cần Thơ, 2019)
The present study was conducted to determine the effects of dietary feed LP20 (20% heat-killed Lactobacillus plantarum, HK L-137) on growth performance, immune response and disease resistance of juvenile striped catfish (Pangasianodon hypophthalmus).